Long-term outcomes of laparoscopic liver resection versus open liver resection for hepatocellular carcinoma: A single-center 10-year experience - Tian, Feng; Leng, Songyao; Chen, Jian; Cao, Yong; Cao, Li; Wang, Xiaojun; Li, Xuesong; Wang, Juan; Zheng, Shuguo; Li, Jianwei (Frontiers in Oncology, 2023)
Background: Laparoscopic liver resection (LLR) for hepatocellular carcinoma (HCC) has increased. However, the long-term outcomes of LLR for HCCs should be validated further. Besides, the validity of laparoscopic minor liver resection in difficult segments (1, 4a, 7, 8) (LMLR-DS) and laparoscopic major hepatectomy (LMH) for HCCs need to be studied. Methods: A total of 1773 HCC patients were collected: 683 received LLR and 1090 received OLR. Propensity score matching (PSM) with 1:1 ratio was used to eliminate the selection bias. Short-term and long-term outcomes were compared. In subgroup analyses, the validity of LMLR-DS or LMH for HCCs was studied. Results: After PSM, 567 patients were in LLR or OLR group. LLR had lower intraoperative blood-loss and shorter postoperative hospital-stays than OLR. The postoperative complications were lower in LLR group (23.8% vs. 32.8%, P=0.001). The Overall survival (OS) and disease-free survival (DFS) had no significant difference between LLR and OLR groups (P=0.973, P=0.812). The cumulative 1-, 3-, and 5-year OR rates were 87.9%, 68.9%, and 57.7% for LLR group, and 85.9%, 68.8%, 58.8% for OLR group. The cumulative 1-, 3-, and 5-year DFS rates were 73.0%, 51.5%, 40.6% for LLR group, and 70.3%, 49.0%, 42.4% for OLR group. In subgroup analyses, 178 patients were in LMLR-DS or open surgery (OMLR-DS) group after PSM. LMLR-DS had lower intraoperative blood-loss and shorter postoperative hospital-stays than OMLR-DS. The postoperative complications were lower in LMLR-DS group. The OS and DFS had no difference between LMLR-DS and OMLR-DS groups. The cumulative 5-year OR and DFS rates were 61.6%, 43.9% for LMLR-DS group, and 66.5%, 47.7% for OMLR-DS group. In another subgroup analyses, 115 patients were in LMH or open major hepatectomy (OMH) group. LMH had lower blood-loss and shorter postoperative hospital-stays than OMH. The complications, OS and DFS had no significantly differences between two groups. The cumulative 5-year OR and DFS rates were 44.3%, 29.9% for LMH group, and 44.7%, 33.2% for OMH group. Conclusions: LLR for HCCs showed better short-term outcomes and comparable long-term outcomes with OLR, even for patients who received LMLR-DS or LMH. LLR could be reliable and recommended for HCC treatment.